The market for wastewater sludge (biosolids) - Villy Søgaard (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2016)
Despite public approval from the Danish Environmental Protection Agency (Miljøstyrelsen), farmers have proven reluctant to accept wastewater sludge as a source of fertilizer. They are in fact still being paid for accepting it. Based on interviews with key stakeholders, a review of the literature, and theoretical reflections this paper analyses the barriers to the recycling of wastewater sludge.
Keywords: Q13; Q15; Q21; Q24; Q25; Q53; Q55; 330; sludge; recycling; wastewater treatment